1995
DOI: 10.1002/1097-0142(19951015)76:8<1481::aid-cncr2820760828>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus–associated leiomyosarcomas in liver transplantation recipients. Origin from either donor or recipient tissue

Abstract: Background. Leiomyosarcoma, a mesenchymal malignancy with smooth muscle differentiation, is extremely rare in children. Immunosuppression, due to either antirejection medication in organ transplantation recipients or human immunodeficiency virus infection (HIV), appears to constitute a predisposition. Methods. Two cases of leiomyosarcoma in pediatric liver transplantation recipients were investigated and compared clinically with respect to site of origin and course of the disease and pathologically by routine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 26 publications
1
66
0
Order By: Relevance
“…There have been very few documented cases of nonlymphoid solid organ tumors of donor origin reported following liver transplantation (11)(12)(13)(14)(15)(16)(17)(18)(24)(25)(26)(27)(28). These cases have included donor transmitted neuroendocrine carcinoma (13), Kaposi's sarcoma (17), leiomyosarcoma (16), melanoma (11), adenocarcinomas (18,26), glioblastomas (15,27,28), and choriocarcinomas (12,14,24,25) Our case represents such a case and, to our knowledge, is the only reported case of donor-transmitted SCC occurring in a transplanted liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been very few documented cases of nonlymphoid solid organ tumors of donor origin reported following liver transplantation (11)(12)(13)(14)(15)(16)(17)(18)(24)(25)(26)(27)(28). These cases have included donor transmitted neuroendocrine carcinoma (13), Kaposi's sarcoma (17), leiomyosarcoma (16), melanoma (11), adenocarcinomas (18,26), glioblastomas (15,27,28), and choriocarcinomas (12,14,24,25) Our case represents such a case and, to our knowledge, is the only reported case of donor-transmitted SCC occurring in a transplanted liver.…”
Section: Discussionmentioning
confidence: 99%
“…Discovery of a donor-derived malignancy in an allograft is a very unusual occurrence following solid organ transplantation. Many of these tumors are lymphoproliferative, however, cases of various nonlymphoid donor-derived malignancies developing in solid organ recipients have also been described (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Establishing the origin of malignancy can be very difficult yet has significant implications for successful treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The smooth muscle tumors can occur in peripheral soft tissue, intracranial space, or visceral sites, and tumor multiplicity is common. [76][77][78][79][80][81][82][83][84][85] Molecular genetic analysis has shown that multiple tumor represent independent clones rather than dissemination of a single neoplastic clone. 85 In multiple tumor cases, tumors arising in the transplant are of donor cell origin, whereas those at the other sites arise from recipient cells, which also points to polyclonal origin of multiple tumors.…”
Section: Ebv-associated Smooth Muscle Tumorsmentioning
confidence: 99%
“…85 In multiple tumor cases, tumors arising in the transplant are of donor cell origin, whereas those at the other sites arise from recipient cells, which also points to polyclonal origin of multiple tumors. 82 Although these tumors were originally divided into EBV-associated leiomyomas and leiomyosarcomas, current classification holds them all collectively as smooth muscle tumors as they are usually indolent although somewhat unpredictable in behavior. True metastatic behavior is rare, and was observed only in 4 of 51 AIDS-associated (8%) 77 and 1 of 19 cases (5%) in a mixed AIDS and transplantation-associated series.…”
Section: Ebv-associated Smooth Muscle Tumorsmentioning
confidence: 99%
“…Their multifocal nature is thought to be the result of multiple independent infections, rather than metastasis (6). Despite the multifocal nature of the disease, EBV-SMTs mostly appear to be indolent and discovered by means of surveillance imaging studies, especially in the absence of intracranial involvement (8,21). However, fever, abdominal pain, anorexia, weight loss, graft dysfunction, neurologic symptoms and pulmonary symptoms has been reported (8,(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%